The type specimens and type localities of the orangutans, genus Pongo Lacépède, 1799 (Primates: Hominidae). Issue 33 (9th September 2016) - Brandon-Jones, Douglas; Groves, Colin P.; Jenkins, Paulina D.
ABSTRACT: Uncertain type localities undermine orangutan nomenclature. Bequeathed to the British Museum, the holotype of Pongo pygmaeus, according to Hans Sloane's catalogue, came from Borneo and died in China. The historical evidence makes Banjarmasin its most probable type locality. William Montgomerie, Assistant Surgeon at Singapore from 1819–1827, and Senior Surgeon from 1832, supplied the holotype of Simia morio . In 1836 an adult female orangutan reached Singapore alive from Pontianak, Borneo. The holotypes of S. morio, S. hendrikzii, S. straussii and P [ ithecus ] owenii probably had the same origin, as pirate attacks endangered visits to other Bornean coasts. Absent from Brunei and north Sarawak, Malaysia, throughout the Holocene, orangutans occur there only as Pleistocene subfossils at Niah. Pan vetus (the Piltdown mandible) probably came from Paku, Sarawak. We identify Pongo borneo Lacépède, 1799 as an objective senior synonym of P. wurmbii Tiedemann, 1808, correcting its type locality from Sukadana to near Pontianak. This is the earliest name for the western subspecies (previously thought nominotypical) unless Pithecus curtus, probably from the Sadong River, Sarawak, represents a separate subspecies. If so, the name Pongo borneo would transfer to the southern population west of the Kahayan River, genetically distinguished at species level from the Sumatran orangutan, P. abelii .